solving equations by sibstitution
posted by Anonymous on .
2x+6y=6
7x+8y=5

multiply the top by positive 8 and multiply the bottom by negative 6. then cancel out the y's and solve for x. plug x back into anyone and solve for y.

hmm. sounds like elimination to me.
For substitution, pick either equation and solve for x (or y):
2x+6y=6
6y = 2x+6
y = x/3 + 1
Now substitute that into the other equation:
7x+8y = 5
7x + 8(x/3 + 1) = 5
7x + 8x/3 + 8 = 5
13x/3 = 13
x = 3
so, y = x/3+1 = 2
be sure to plug (3,2) into the original equations to make sure you (or I!) didn't make a mistake.